Myth and Reality about the Origin of Inductive Loops in Impedance Spectra of Lithium-Ion Electrodes — A Critical Experimental Approach. (20th July 2016) - Brandstätter, Harald; Hanzu, Ilie; Wilkening, Martin
Abstract: Electrochemical Impedance Spectroscopy (EIS) is a sophisticated analyzing tool in battery research. Though, there are still phenomena subject to speculation. As an example, for a long time the formation of the so-called Solid Electrolyte Interphase (SEI) has been made responsible for inductive loop formation in impedance spectra. In our opinion, there are, however, no satisfying evidences supporting this attempt to explain the occurrence of inductive loops. The present study is, thus, aimed at answering the question whether other origins such as cell design ought to be considered to reveal the electrical sources for this phenomenon. Therefore, two commonly used anode materials for lithium-ion batteries were investigated with respect to their tendency to the formation of SEIs. Besides the influence of the SEI on the overall impedance response, also the impact of the cell design on electrical response was investigated. We identified four different sources of (i) inductive and (ii) negative capacitance loop formation: springs, reference electrodes, drift, and corrosion. In conclusion, any interrelationship between inductive loops and SEI formation could be ruled out. This finding disproves an earlier, commonly known attempt that traced the presence of inductive loops back to the formation of passivating surface layers because of electrolyte decomposition.